Integrating causal pathway diagrams into practice facilitation to address colorectal cancer screening disparities in primary care - Brooke Ike; Ashley Johnson; Rosemary Meza; Allison Cole (BMC, 2024)
Abstract Background Colorectal cancer (CRC) is the second leading cause of cancer death and the second most common cancer diagnosis among the Hispanic population in the United States. However, CRC screening prevalence remains lower among Hispanic adults than among non-Hispanic white adults. To reduce CRC screening disparities, efforts to implement CRC screening evidence-based interventions in primary care organizations (PCOs) must consider their potential effect on existing screening disparities. More research is needed to understand how to leverage existing implementation science methodologies to improve health disparities. The Coaching to Improve Colorectal Cancer Screening Equity (CoachIQ) pilot study explores whether integrating two implementation science tools, Causal Pathway Diagrams and practice facilitation, is a feasible and effective way to address CRC screening disparities among Hispanic patients. Methods We used a quasi-experimental, mixed methods design to evaluate feasibility and assess initial signals of effectiveness of the CoachIQ approach. Three PCOs received coaching from CoachIQ practice facilitators over a 12-month period. Three non-equivalent comparison group PCOs received coaching during the same period as participants in a state quality improvement program. We conducted descriptive analyses of screening rates and coaching activities. Results The CoachIQ practice facilitators discussed equity, facilitated prioritization of QI activities, and reviewed CRC screening disparities during a higher proportion of coaching encounters than the comparison group practice facilitator. While the mean overall CRC screening rate in the comparison PCOs increased from 34 to 41%, the mean CRC screening rate for Hispanic patients did not increase from 30%. In contrast, the mean overall CRC screening rate at the CoachIQ PCOs increased from 41 to 44%, and the mean CRC screening rate for Hispanic patients increased from 35 to 39%. Conclusions The CoachIQ program merges two implementation science methodologies, practice facilitation and causal pathway diagrams, to help PCOs focus quality improvement efforts on improving CRC screening while also reducing screening disparities. Results from this pilot study demonstrate key differences between CoachIQ facilitation and standard facilitation, and point to the potential of the CoachIQ approach to decrease disparities in CRC screening.